GERONTOINFO: Sistema de información para la investigación en gerontopsiquiatría del Hospital Infantil Universitario de San José. - Rodríguez Angarita, Carlos E.; Rueda Reatiga, Lina María; Santa Villamil, Carlos Alberto (Revista Médica de Risaralda)
Background: This study presents the development of GERONTOINFO, an information system designed exclusively for research in gerontopsychiatry at the San José University Children's Hospital. The system was created to overcome challenges arising from the diversity of pathologies and to standardize the collection of clinical data, enabling the structured gathering, storage, and analysis of information with high-security standards. Methodology: This is an applied research study focused on software development and technological evaluation in mental health. Initially, a thorough analysis of the service's needs and requirements was conducted to define the critical areas of data management. Subsequently, a modular architecture was designed and developed using Node.js and MySQL to securely and efficiently integrate multiple modules, such as the management of personal data, clinical history, mental examinations, assessment scales, and psychometric test results. Results: During the implementation phase, pilot usability tests were conducted using the System Usability Scale (SUS), yielding an average score of 88 from a sample of ten researchers, indicating high acceptance and ease of use. Additionally, security measures such as data encryption and automatic backups were implemented to ensure the integrity and confidentiality of the collected information. Conclusion: GERONTOINFO emerges as a specialized and efficient tool for research in gerontopsychiatry, significantly improving the quality of clinical information and laying the groundwork for more robust studies in this field. Its continuous evolution, with potential artificial intelligence integrations, promises to further enhance its capacity to optimize data management and analysis in gerontopsychiatry.